Wear properties of aluminium silicon carbide (AISiCp), metal matrix composite - 379708 Ahmad Zamri Mohamad (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Enginerring (Mechanical - Materials)) - Universiti Teknologi Malaysia, 2004